Influence of Structure and Composition of Polymer Nanocomposites with Carbon and Hybrid Fillers on the Efficiency of Electromagnetic Shielding. Issue 1 (13th April 2023) - Mamunya, Yevhen; Sushko, Oleksandr; Maruzhenko, Oleksii; Paraschenko, Iryna; Pylypenko, Andrii; Dubrovka, Fedir
Abstract: The shielding efficiency (absorption SEA, reflection SER, and total SET ) and conductivity of composites based on organic–inorganic polymer matrix (OIM) and polyethylene (UHMWPE) containing mixtures (hybrid fillers) of carbon black (CB), carbon nanotubes (CNT), and iron oxide (Fe2 O3 ) are studied. The best shielding results (SET = 23.1 dB, SEA = 17.7 dB) show a composite based on UHMWPE with a segregated structure of the hybrid filler CNT+CB with a total content of 10 vol%, due to the high electrical conductivity of the composite. It is found a close correlation between the conductivity of the composite and the absorption efficiency SEA which sharply increases when the value of conductivity becomes above 10 −3 S cm −1 . In composites based on OIM with hybrid filler CNT+Fe2 O3, the moderate shielding characteristics are achieved (SET = 12.3–12.7 dB, SEA = 8.8–9.2 dB), but they have the conductivity more than two orders of magnitude lower than the composites with carbon fillers. This effect arises due to the additional contribution to the absorption efficiency of the interaction of ferromagnetic non‐conductive oxide with the magnetic component of electromagnetic wave. Such composites have the potential to achieve high shielding performance at determining the optimal composition of the hybrid filler.